Chronische Analfissur - salben oder schneiden?: Leitthema - Klein, Marie; Zadnikar, Marcel; Marti, Lukas (Die Chirurgie, 2025)
An anal fissure is a painful lesion of the anal canal. The acute form often heals spontaneously and should be treated conservatively. The treatment of chronic anal fissures is the subject of many studies but the treatment recommendations of international guidelines are contradictory. Conservative treatment consists of chemical sphincterotomy using sphincter-relaxing drugs, such as calcium channel antagonists, nitrates or botulinum toxin and leads to healing in only about 50% of patients with a prolonged healing time and a high rate of recurrence. In contrast surgical treatment is much more effective. Lateral internal sphincterotomy is the most effective treatment with a success rate of >90%. Fissurectomy with a success rate of 80% is preferred in German-speaking countries due to its much lower risk of incontinence.
Online publiziert: 18. Juli 2025
Gesehen am 09.09.2025